Process conditions of spray drying microencapsulation of Nigella sativa oil - Mohammed, Nameer Khairullah; Tan, Chin Ping; Abd Manap, Mohd Yazid; Alhelli, Amaal Mohammedalaa; Meor Hussin, Anis Shobirin (Elsevier BV, 2017)
Microencapsulation is an excellent substitute in the transformation of liquid food into stabilised powder. The objective of the present study was to examine the influence of process conditions on microencapsulation of Nigella sativa oil using spray drying, by applying the response surface methodology (RSM) by central composite design. The independent variables were: the content of wall material (10–30%), the concentration of oil (10–30%) and temperature (150–190 °C of inlet air drying). The microencapsulation efficiency, moisture content, solubility, particle size, total phenolic content (TPC), and antioxidant activity by 1,1-diphenyl-picryl-hydrazyl (DPPH) were analysed as responses. Powders were gauged by a complete 23 central composite rotatable design. The optimal conditions were determined to be 30% wall material, 10% concentration of oil, and 160 °C drying inlet air temperature. The optimised spray-dried powder had high values for MEE (92.71%), solubility (91.38%), and total phenolic content TPC (137.68 mg/100 g) as well as low values of DPPH (IC50 of 1.61 mg/g), moisture content (1.03%), and particle size (15.516 μm).